2003
DOI: 10.1097/00024382-200304000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of N-Acetylcysteine on Apoptotic Lung Injury in Cecal Ligation and Puncture-Induced Sepsis Model

Abstract: Apoptotic loss of parenchymal cells may lead to organ dysfunctions in critically ill patients with septic states. As an antioxidant, the protective effects of N-acetylcysteine (NAC) are documented in many experimental and clinical studies. In this experimental study, we investigated the role of chronically used NAC in septic lung injury on a cecal ligation and puncture (CLP) model. To evaluate this, 30 male Wistar rats were randomly divided into four groups as sham (n = 7), CLP (n = 8), sham + NAC (n = 7) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
61
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(77 citation statements)
references
References 29 publications
8
61
0
5
Order By: Relevance
“…[17] In another experimental sepsis model created by endotoxin administration to rats, it was found that histopathological findings such as alveolar and interstitial hemorrhage and edema and leukocyte infiltration improved in groups treated with high doses of NAC. [18] In our study, in the histopathological examination of the lungs, the increase in PMNL was found to have significantly decreased in the NAC group compared to the sepsis group. The improvements in congestion, hemorrhage and septal thickening in the lung tissue and the histological improvements in the kidney and the liver were not statistically significant.…”
Section: Discussionsupporting
confidence: 47%
“…[17] In another experimental sepsis model created by endotoxin administration to rats, it was found that histopathological findings such as alveolar and interstitial hemorrhage and edema and leukocyte infiltration improved in groups treated with high doses of NAC. [18] In our study, in the histopathological examination of the lungs, the increase in PMNL was found to have significantly decreased in the NAC group compared to the sepsis group. The improvements in congestion, hemorrhage and septal thickening in the lung tissue and the histological improvements in the kidney and the liver were not statistically significant.…”
Section: Discussionsupporting
confidence: 47%
“…Other studies also confirm the protective role of NAC in lung cell death in experimental models of sepsis 18,22,23 .…”
Section: Discussionmentioning
confidence: 57%
“…However, there is evidence that NAC is able to attenuate apoptosis of lung epithelial cells in experimental models of sepsis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A tissue damage evaluation scale was used as was stated in an article by Özdülger et al (12). In this scale:…”
Section: For the Lungsmentioning
confidence: 99%